A pattern language for living well with dementia: Words for a Journey. (2016) - Iba, Takashi; Matsumoto, Aya; Kamada, Arisa; Tamaki, Nao; Kaneko, Tomoki; Okada, Makoto
In this paper, we present a pattern language comprising 40 patterns for living well with dementia. These patterns have been developed based on interviews with people with dementia, their families and people who support them. This paper summarises the pattern language by providing an example and describing its development process. We also present the analysis of feedback from readers, indicating that this pattern language is acceptable to people with dementia and their families and care staff; moreover, these groups could imagine situations where they used the presented patterns to improve and talk about their life with dementia.